2020
DOI: 10.3390/su12083168
|View full text |Cite
|
Sign up to set email alerts
|

Can CEO’s Humble Leadership Behavior Really Improve Enterprise Performance and Sustainability? A Case Study of Chinese Start-Up Companies

Abstract: The relationship between the leadership behavior of a chief executive officer (CEO) and start-up enterprise performance is key to effecting the survival and development of start-ups in the era of the internet economy. Currently, most studies on this topic focus more on the role of leadership effectiveness but rarely explore the CEO’s humility in leadership and the mechanism of its behavior affecting enterprise performance and its sustainable development. Based on leadership theory and upper-echelon theory, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Therefore, EA affects RF, and through it, existing flexible resources can be more easily used for new purposes, thereby expanding the scope of resource use, reducing the cost and difficulty of resource conversion among different purposes, shortening the conversion time and promoting the generation of creative behaviors [54,55]. On the one hand, RF can enhance the technical diversity of internal resources and expand the scope of resource exploration.…”
Section: The Mediating Role Of Resource Flexibilitymentioning
confidence: 99%
“…Therefore, EA affects RF, and through it, existing flexible resources can be more easily used for new purposes, thereby expanding the scope of resource use, reducing the cost and difficulty of resource conversion among different purposes, shortening the conversion time and promoting the generation of creative behaviors [54,55]. On the one hand, RF can enhance the technical diversity of internal resources and expand the scope of resource exploration.…”
Section: The Mediating Role Of Resource Flexibilitymentioning
confidence: 99%
“…With the proliferation of start-ups in the past few years (Pomerol, 2018; Wallin et al, 2018), the world is experiencing an interesting entrepreneurial revolution where entrepreneurs are adding a significant share to the economic growth of their nations (Kuratko, 2007). The creation and sustenance of a new start-up venture call for dedicated vision along with the art of leading and transforming that vision into a reality (Jensen & Luthans, 2006a; Ren et al, 2020; Zaech & Baldegger, 2017). Leadership is of high relevance for the success of start-ups as their foundation and development are inevitably connected with it.…”
Section: Introductionmentioning
confidence: 99%
“…For corporate sustainable growth, the effects of CEO demographic characteristics such as age (Garces-Galdeano and Garcia-Olaverri, 2019; Malik et al , 2020), education (Garces-Galdeano and Garcia-Olaverri, 2019; Malik et al , 2020) and gender (Gatautis et al , 2019) and managerial characteristics such as tenure (Malik et al , 2020) and duality (Nassem et al , 2020), as well as psychological traits such as overconfidence (Guo and Ding, 2019) or humbleness (Ren et al , 2020), narcissism (Kashmiri et al , 2017) and personality (Wang and Chen, 2020) and ethics (Zhao et al , 2020) were repeatedly reported in previous studies. Through in-depth analysis, we can find that the essence of the fore-mentioned CEO demographic and managerial characteristics is the one’s education experience, management skills and the cognitive capabilities increasing with the growth of age.…”
Section: Literature Reviewmentioning
confidence: 80%